40.3: Invisibility Mechanism Research of Metal Bridge in Capacitive Touch Panel and Optimal Design Solution. (28th November 2018) - Xie, Xiaodong; Yang, Hong; Shao, Xibin; Guo, Zongjie; Zhang, Lei; He, Min; Xu, Shifeng; Wang, Jing; Pang, Bin
Abstract : This paper shows deep analysis and research for the invisibility mechanism in large size capacitive touch panel. Invisibility of metal bridge is influenced by LCD module and touch panel together, main factors should be studied together. Experimental verification results show that: (1) when the PPI of LCD module is lower, the area of the LCD Dot occupied by the metal bridge is smaller, then the invisibility effect will be better. (2) The bigger pitch of touch panel pattern will result in the lower density of metal bridge. (3) The invisibility of touch panel also can be improved by the angle change of metal bridge especially when the bridge has intersection angle with LCD RGB dot from 15° to 45°. (4) The width of hammer in metal bridge plays a good role for invisibility, and the improvement effect will not be obvious in a certain width. (5) Whether the direction of the metal bridge and the RGB unit is vertical or parallel almost has no impact on the invisibility. These conclusions can provide references for the follow up product development.